Real Solution Time Discrete System at The Difference Linear Equation Model - Onoy Rohaeni (Matematika, 2010)
ABSTRACT. The difference equation is a model of time sequence domain that useful to define the characteristics of input and output from a time discreet system. Abstractly, it is a relation between the sequence input and output. In this paper, will be shown how to a sequence input uk from the block diagram or the graphics signal flow transformed into a sequence output yk, in which the modeling is used the linear equation by constant coefficients.Keywords: sequence, linear system, discreet time.